2017
DOI: 10.1149/2.0641701jes
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Model for Interpreting the Reaction–Diffusion Characteristics of Li-Air Batteries

Abstract: With the goal of creating a model of a Li-air battery that is consistent with voltammetry data, we develop a full battery model capable of giving insight into details of cell operation otherwise inaccessible to common experimental techniques. With this model, we investigate the dependence of the current on: the diffusion characteristics of the electrolyte, the solubility of the ambient oxygen, the structure of the cathode, and aspects of the primary surface reaction. We explore modifications to a basic reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…The internal mass transfer has been considered in a vast number of heterogeneous catalysis studies in different applications ranging from bio-applications 1,2 and biomass upgrading 3 to thermal catalysis [4][5][6][7][8] and energy materials [9][10][11][12] . The internal transport effect in porous catalytic materials is studied in a reaction-diffusion phenomenon where it is coupled with the intrinsic kinetics of the catalysts 13 .…”
Section: Introductionmentioning
confidence: 99%
“…The internal mass transfer has been considered in a vast number of heterogeneous catalysis studies in different applications ranging from bio-applications 1,2 and biomass upgrading 3 to thermal catalysis [4][5][6][7][8] and energy materials [9][10][11][12] . The internal transport effect in porous catalytic materials is studied in a reaction-diffusion phenomenon where it is coupled with the intrinsic kinetics of the catalysts 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Due to its high gravimetric theoretical capacity up to ∼3000 Wh/kg, the Li–O 2 battery is regarded as a promising candidate to meet the demands of high endurance electrical vehicles. , However, the practical discharge capacity of state-of-the-art Li–O 2 batteries (about 500 Wh/kg) is still far from the theoretical value due to several performance limiting factors, such as the electrode surface passivation by the Li 2 O 2 formed during discharge, the O 2 diffusion in the electrolyte and the electrolyte stability. Moreover, it is found that the performance of a Li–O 2 cell and the morphology of Li 2 O 2 depend on multiple factors including the discharge rate, the type of electrolyte, and the surface properties of the electrode. Besides, it has been reported that strategies like preseeding the electrode by adding seed crystals or predischarging the cell at low potential have significant impacts on the discharge capacity. More fundamental knowledge of the discharge mechanism is then required to enhance the performance of Li–O 2 batteries, and multiscale modeling is revealed as a useful tool to rationalize the experimental observations. However, mathematical models reported in the literature consider oversimplified discharge mechanisms, and therefore, there is a lack of versatile models able to predict the discharge trends with respect to multiple experimentally controllable parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Through a combination of techniques, e.g. ab initio calculations to provide fundamental parameters to molecular dynamics which, in turn, provides transport coefficients to a reaction-diffusion model of the full-scale battery, 2 we can predict battery performance. These predictions can be compared with limited experiments for validation before selecting the best candidates for intensive development.…”
mentioning
confidence: 99%